Building Tourism With the Community: A Study of Local Participation Building a Tourism Village Based on Value Co Creation - Nawangsih Nawangsih (Mahameru Publisher, 2022)
The concept of value co ceation emphasizes the different value aspects created by tourism actors (local communities) and tourists, which are carried out together to develop or provide added value to tourist villages a form of local community participation in building a value co-creation-based tourism village. Qualitative research methodology, using the literat-review method of several journals relevant to the theme of research conducted by both national journals. The results study indicate several factors to identify the potential /opportunities for the formation of a tourist village, including tourist attractions, natural resources, tourism support facilities, preservation of traditional arts, religion, facilities and infrastructure, accommodation and hospitality as well as adjustment of new rules by following strict health protocols following the principles of Cleanliness, Health, Safety and Environmental Sustainability. While the challenges/problems of forming a tourist village consist of limited knowledge and information, low quality of human resources, limited knowledge of destination management, conflicts of interest and hegemony of power, lack of public awareness, limited access to tourist destinations, limited facilities, and infrastructure, the level of community participation is still low, collaboration or synergy with various parties is still low.